Sports Sponsoriing – Part of Corporate Strategy - Varmus, Michal; Lendel, Viliam; Soviar, Jakub; Vodak, Josef; Kubina, Milan (Communications - Scientific letters of the University of Zilina, 2016)
Sponsoring is closely connected with sports and is often incorrectly seen as mere paid advertising. In this article we focused on sponsoring and how it is understood and perceived by Slovak marketing managers and the business community. Based on a survey, interviews and literature analysis we highlighted the strategic aspect of sponsoring in relation to the companies and sports clubs. We focused only on the main factors related to sponsoring. This article also represents a basis for further research in order to better define approaches and motivational aspects of sponsoring.